Pemanfaatan Penguasaan Komputer Dalam Menghadapi Ujian Berbasis Komputer Bagi Siswa - Alfa Saleh; Ria Eka Sari; Jodi Orlando Manihuruk (LPPM STIKOM Tunas Bangsa, 2020)
The rapid growth of technology and information at this time is really very easy for humans to find and gather information, of course the use of computers as media in obtaining such information is needed. That development also finally had a good impact in several sectors of life, one of which was in the education sector. The use of computers has become indispensable at this time, as evidenced by the existence of a number of computer systems in the implementation of education to migrate for the better, such as the implementation of examinations with a computer based system. However, it seems that this was not welcomed by students due to the low level and the lack of understanding of students in terms of computer mastery, so that computer-based exams became quite difficult for these students. To improve the ability of students in computer mastery, especially students in the Amal Bakti Private High School (SMA) Medan, this community service was carried out. As a result, students' understanding has improved and they have become accustomed to using computers.